Illocutionary speech acts in the lyrics of Indonesian national songs with themes of struggle - Tanty Aidullia Nasution; Erikson Saragih; Peni Bernita Bangun (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2026)
National songs function not only as works of art but also as a medium of pragmatic communication imbued with national values. This study aims to analyze the illocutionary speech acts found in the lyrics of Indonesian national songs themed around struggle. The research employed a descriptive qualitative approach based on the speech act theories of Austin (1962) and Searle (1979). The data consisted of song lyrics containing illocutionary speech acts, drawn from Indonesian national songs. Data were collected through several qualitative stages, namely source identification, text documentation, close reading, initial coding, and data recording. The data were analyzed inductively in order to interpret meanings based on the results of the analysis within the context of struggle and speech acts. The findings reveal that all five types of illocutionary speech acts were identified in the song lyrics: assertives (11), directives (12), commissives (15), expressives (8), and declaratives (1). Functionally, songs of struggle serve to mobilize the people, reinforce pledges, express emotions, affirm identity, and legitimize independence. These findings extend previous studies that focused only on a single type of illocutionary act by demonstrating that national songs contain the full range of illocutionary acts, functioning as instruments of national rhetoric and character education. Therefore, songs of struggle are not only aesthetically valuable but also performative in shaping the spirit of nationalism.